Project Based Learning Model to Increase Scientific Process Skills and Knowledge Learning Outcomes of Students on Colloid System - Ellisa Nurramadhani; Leny Leny; Mahdian Mahdian (Universitas Lambung Mangkurat, 2023)
The lack of students' scientific process skills on colloidal system material causes less active behavior in the learning process which results in the quality of low knowledge learning outcomes. This study aims to improve students' scientific process skills and knowledge learning outcomes on colloidal system material. This study employed experimental research and quasi-experimental methods. The research subjects in the experimental and control classes were 33 people in total. The data collection techniques used were test and non-test techniques. Test instruments included scientific process skills test instruments and knowledge learning outcomes, while non-test instruments were observation sheets and response questionnaires. The factors studied were (1) scientific process skills, (2) knowledge learning outcomes and (3) responses. Data analysis techniques used descriptive and inferential analysis techniques. The results showed that there was an increase in scientific process skills and knowledge learning outcomes after applying the Project Based Learning model (PjB). The results of the increase in scientific process skills with indicators measured, namely: observing, predicting, classifying, interpreting, and communicating were 43.95, 50.90, 55.76, 59.10. The percentage of knowledge results amounted to 85.15% and the results of the questionnaire response amounted to 90.91% with a positive category. It can be inferred that the PjBL model can improve students' scientific process skills and knowledge learning outcomes on colloidal system material.